2012
DOI: 10.1093/toxsci/kfs084
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Factors Induce Coronary Endothelial Cell Activation Following Exposure to Inhaled Diesel Exhaust and Nitrogen Dioxide in Humans: Evidence From a Novel Translational In Vitro Model

Abstract: The vascular toxicity of inhaled agents may be caused by soluble factors that are released into the systemic circulation. To confirm this in a straightforward manner, we obtained plasma from healthy human volunteers before and after exposure to diesel exhaust (DE) and nitrogen dioxide (NO(2)). Plasma samples were obtained from human volunteers exposed to 100 μg/m(3) DE or filtered air for 2 h. A second cohort was exposed to 500 ppb NO(2) or filtered air in an identical protocol. Primary human coronary artery e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
73
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(83 citation statements)
references
References 31 publications
9
73
1
Order By: Relevance
“…Dose-related endothelial and inflammatory responses were also found in the range 2.6-10.6 ppm. Channell et al (2012) found that plasma from healthy adults exposed to 0.5 ppm NO 2 for 2 hours was able to activate cultured primary human coronary endothelial cells. This suggested that a circulating factor was mediating, at least in part, the endothelial response that may underly the cardiovascular epidemiological findings.…”
Section: Toxicological Studies On Short-term Exposure (Hours To Days)mentioning
confidence: 95%
See 1 more Smart Citation
“…Dose-related endothelial and inflammatory responses were also found in the range 2.6-10.6 ppm. Channell et al (2012) found that plasma from healthy adults exposed to 0.5 ppm NO 2 for 2 hours was able to activate cultured primary human coronary endothelial cells. This suggested that a circulating factor was mediating, at least in part, the endothelial response that may underly the cardiovascular epidemiological findings.…”
Section: Toxicological Studies On Short-term Exposure (Hours To Days)mentioning
confidence: 95%
“…A study in mice suggested that effects in the lung due to 20 ppm NO 2 for 10 days are worse with a small increase in vitamin C dose than with a large increase (Zhang et al, 2010), perhaps due to vitamin C increasing NO 2 absorption into the epithelial lining fluid (Enami, Hoffmann & Colussi, 2009). All these concentrations (apart from Channell et al, 2012) are far in excess of the ambient concentrations linked to health effects in population studies, and the studies are not designed to show whether the mechanisms extend down to lower concentrations -that is, the mechanisms may or may not be relevant.…”
Section: Toxicological Studies On Short-term Exposure (Hours To Days)mentioning
confidence: 99%
“…We used cultured mouse cerebrovascular endothelial cells (mCECs) as biosensors of cumulative inflammatory mediators in serum from MWCNT-exposed mice, an approach that has proven valuable in toxicologic and clinical applications (16,28). Microarray analysis was performed on mRNA isolated from primary mCECs following incubation with serum collected from MWCNT-or DM-exposed mice (at 4 h postexposure) at 10% in medium for 4 h (Fig.…”
Section: Evidence Of Broad Cerebrovascular Bbb Disruption and Glialmentioning
confidence: 99%
“…Despite their very limited ability to translocate beyond the lung (12), MWCNTs have been shown to induce extrapulmonary toxicity through as-yet unknown pathways (13)(14)(15). Pulmonary interactions with inhaled pollutants, including MWCNTs, can generate secondary bioactive factors that spill over into the systemic circulation and are distributed throughout the body (15)(16)(17). One consequence of these circulating factors is activation of the endothelium, characterized by the expression of adhesion molecules and recruitment/activation of circulating inflammatory cells (18).…”
mentioning
confidence: 99%
“…The DEP-bound PAHs include high molecular weight PAHs with more carcinogenic potency (such as BaA, CHR, BbF, BaP, and IND) (Kerminen et al, 1997;Soontjens et al, 1997). Therefore, the exposure to the emission environment of diesel engines increases the risk of the occurrence of cardiovascular diseases, respiratory diseases, and lung cancer that negatively affect human health (Sultan, 2007;Channell et al, 2012).…”
Section: Introductionmentioning
confidence: 99%